2004
DOI: 10.1079/bjn20031027
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant supplementation preserves antioxidant response in physical training and low antioxidant intake

Abstract: The present controlled-training double-blind study (supplemented (S) group, n 7; placebo (P) group, n 10) was designed to investigate whether an antioxidant mixture (Se 150 mg, retinyl acetate mg, ascorbic acid 120 mg, a-tocopheryl succinate) would allow overloaded triathletes to avoid adaptation failure in the antioxidant system. Dietary intakes were recorded. The supplement of Se, and vitamins A and E provided 100 % of the French RDA. Four weeks of overloaded training (OT) followed 4 weeks of normal training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 40 publications
1
57
0
5
Order By: Relevance
“…However, below and above a stimulation threshold triggered by a given load, the relationship between training loads and endogenous adaptation is not verified (76,90) . An interdependence of antioxidant intakes and the effects of training on the endogenous antioxidant system has been observed in reference to a training-load modulation (increase/ decrease) (7,76) . This supposes that the antioxidants required during a period of increased or reduced training stress differ from those required during a 'normal' training period.…”
Section: Seleniummentioning
confidence: 99%
See 3 more Smart Citations
“…However, below and above a stimulation threshold triggered by a given load, the relationship between training loads and endogenous adaptation is not verified (76,90) . An interdependence of antioxidant intakes and the effects of training on the endogenous antioxidant system has been observed in reference to a training-load modulation (increase/ decrease) (7,76) . This supposes that the antioxidants required during a period of increased or reduced training stress differ from those required during a 'normal' training period.…”
Section: Seleniummentioning
confidence: 99%
“…One has to be cautious when interpretating plasma a-tocopherol concentrations during training periods. Indeed, the higher the intensity in training is, the higher plasma a-tocopherol concentrations are (7) . Exercise mobilises more plasma a-tocopherol and leads to an increase in circulating concentrations (26,27) .…”
Section: Vitamin Ementioning
confidence: 99%
See 2 more Smart Citations
“…One of the possibilities is to associate physical training with antioxidant supplementation. PALAZZETTI et al [163] reported that physical over-training-induced nonenzymatic antioxidant downregulation and increased susceptibility to oxidative damage can be avoided by antioxidant supplementation during the training period.…”
Section: Antioxidant Supplementationmentioning
confidence: 99%